1994
DOI: 10.1093/clinids/18.4.633
|View full text |Cite
|
Sign up to set email alerts
|

Septic Pulmonary Emboli Complicating Mastoiditis: Lemierre's Syndrome Revisited

Abstract: Deep neck-space infections may cause potentially life-threatening complications of head and neck infections. Lateral pharyngeal space infections in particular predispose to development of suppurative jugular vein thrombosis, which may be associated with anaerobic bacteremia and septic pulmonary emboli (Lemierre's syndrome). We describe a case of Lemierre's syndrome, a very rare entity in the antibiotic era, complicating mastoiditis. Surgical debridement and drainage in conjunction with antibiotic therapy resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 5 publications
0
30
0
1
Order By: Relevance
“…To date, there are no published data reporting the relationship between acute pancreatitis and LS. As other reports suggested that septic emboli could metastasize to any part of the body through the blood stream,2, 3, 7, 8 there was a possibility that the patient's acute pancreatitis was caused by the metastatic septic emboli as a part of LS. The learning points from this case are that LS and acute pancreatitis can occur simultaneously and, most importantly, assuming one diagnosis without paying attention to the symptoms not compatible with it (in our case, oropharyngeal symptoms not compatible with acute pancreatitis) can lead to the delayed diagnosis of LS.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…To date, there are no published data reporting the relationship between acute pancreatitis and LS. As other reports suggested that septic emboli could metastasize to any part of the body through the blood stream,2, 3, 7, 8 there was a possibility that the patient's acute pancreatitis was caused by the metastatic septic emboli as a part of LS. The learning points from this case are that LS and acute pancreatitis can occur simultaneously and, most importantly, assuming one diagnosis without paying attention to the symptoms not compatible with it (in our case, oropharyngeal symptoms not compatible with acute pancreatitis) can lead to the delayed diagnosis of LS.…”
Section: Discussionmentioning
confidence: 92%
“…Pathogenesis is associated with pharyngitis affecting the palatine tonsils or peritonsillar tissue 7. Other sources include upper and lower respiratory, mastoiditis, laryngitis, dental, paranasal sinusitis, parotitis, orbital, gastrointestinal, and lip piercing 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thorax CT was taken under emergency conditions (Figures 1-a 1-4 , Figures 2-a [5][6][7][8][9] ) and revealed consolidations and multiple nodular lesions with various sizes (0.5-4cm) some were pleurally based and some were cavitating, randomly dispersed on both lung fields. In the lateral basal segment of the right lung lower lobe there was a wide pleural based consolidation area.…”
Section: Casementioning
confidence: 99%